Eocene “Chusquea” fossil from Patagonia is a conifer, not a bamboo - Wilf, Peter (PhytoKeys, 2020)
Abstract. Chusquea oxyphylla Freng. & Parodi, 1941, a fossilized leafy branch from the early Eocene (52 Ma), late-Gondwanan Laguna del Hunco biota of southern Argentina, is still cited as the oldest potential bamboo fossil and as evidence for a Gondwanan origin of bamboos. On recent examination, the holotype specimen was found to lack any typical bamboo characters such as nodes, sheaths, ligules, pseudopetioles, or parallel leaf venation. Instead, it has decurrent, clasping, univeined, heterofacially twisted leaves with thickened, central-longitudinal bands of presumed transfusion tissue. These and other features allow confident placement in the living Neotropical and West Pacific disjunct genus Retrophyllum (Podocarpaceae), which was recently described from the same fossil site based on abundant, well-preserved material. However, the 1941 fossil holds nomenclatural priority, requiring the new combination Retrophyllum oxyphyllum (Freng. & Parodi) Wilf, comb. nov. No reliable bamboo fossils remain from Gondwana, and the oldest South American bamboo fossils are Pliocene. Chusquea joins a growing list of living New World genera that are no longer included in Paleogene Patagonian floras, whose extant relatives are primarily concentrated in Australasia and Malesia via the ancient Gondwanan route through Antarctica.